Chemical constituents from Polygonatum kingianum Coll. & Hemsl - Huyen, Do Thi Thanh; Phuong, Ngo Thi; Hung, Pham Ngoc; Anh, Bui Kim; Ha, Le Minh (Vietnam Journal of Science and Technology, 2020)
Seven compounds, including two homoisoflavanones 3-(2ʹ-hydroxy-4ʹ-methoxy-benzyl)-5,7-dihydroxy-8-methyl-chroman-4-one (1), disporopsin (2) along with 2-O-methyl-α-D-fructofuranose (3), (E,E)-9-oxooctadeca-10,12-dienoic acid (4), 1-palmitoylglycerol (5), 5α,8α-ergosterol peroxide (6), daucosterol (7) were isolated from the rhizomes of Polygonatum kingianum of Vietnam. Their structures were determined by 1D and 2D NMR spectra and by comparison with the reported spectral data. Compounds 3, 4 and 6 are first reported from the genus Polygonatum. Compound 1 and 5 are reported for the first time from Polygonatum kingianum.